2016
DOI: 10.1007/s13318-016-0385-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vitro Cytochrome P450 Inhibition and In Vitro Fate of Structurally Diverse N-Oxide Metabolites: Case Studies with Clozapine, Levofloxacin, Roflumilast, Voriconazole and Zopiclone

Abstract: Clinical DDI potential of specific CYP enzymes needs to be considered arising due to circulatory concentrations of certain N-oxides depending on the dose size and/or frequency of dosing of the respective parent drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Indeed, Giri et al reported that another N-oxide metabolite-voriconazole N-oxide-was an effective inhibitor of CYP3A4 (IC50 8.7 μM; 36), and there are other CYP-mediated drug metabolites that have been shown to be more effective inhibitors than the parent drugs. These include not only reactive metabolites generated by CYP oxidation of alkylamino, methylenedioxyphenyl, thionosulfur, phenolic, and unsaturated moieties (37-43) but also major isolable metabolites that elicit reversible inhibition of CYPs (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Giri et al reported that another N-oxide metabolite-voriconazole N-oxide-was an effective inhibitor of CYP3A4 (IC50 8.7 μM; 36), and there are other CYP-mediated drug metabolites that have been shown to be more effective inhibitors than the parent drugs. These include not only reactive metabolites generated by CYP oxidation of alkylamino, methylenedioxyphenyl, thionosulfur, phenolic, and unsaturated moieties (37-43) but also major isolable metabolites that elicit reversible inhibition of CYPs (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, hemoglobin tends to be the modulator of voriconazole trough concentration. Voriconazole is primarily metabolized in the liver, and hemoglobin may be involved in the formation of its major metabolite, N-oxide voriconazole (48). Nevertherless, the mechanism of interaction remains unknown.…”
Section: Accepted Articlementioning
confidence: 99%
“…Previously we have executed in vitro experiments to unambiguously evaluate the role of N-oxide metabolites of diversified chemical structures such as clozapine, levofloxacin, roflumilast, voriconazole and zopiclone for the potential CYP inhibition [19]. Accordingly, it was summarized that certain N-oxide metabolites such as clozapine-N-oxide and voriconazole-N-oxide may potentially play a role as a perpetrator drug despite having a higher potency (> 1 µM but < 10 µM) for certain CYP enzymes because the N-oxide metabolites are long-lived and therefore, may potentially accumulate after multiple doses in patients who may further manifest impaired clearance of such N-oxide metabolite(s) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of CYP3A4 by ITZ, OH-ITZ, keto-ITZ, and ND-ITZ was evaluated using hydroxylation of midazolam as a probe reaction, and unbound IC 50 values were 6.1 nM, 4.6 nM, 7.0 nM, and 0.4 nM, respectively. Itraconazole metabolites are equally or more potent CYP3A4 inhibitors than parent itself, and therefore are responsible for in vitro versus in vivo discrepancy observed in CYP3A4 inhibition by ITZ [15, 16]; b) Warfarin: Hydroxywarfarin, the key metabolite showed inhibition of CYP2C9 in vitro (human liver microsomes and recombinant enzymes) [17]; c) Amiodarone: Desethylamiodarone metabolite was shown to inhibit CYP1A1, CYP1A2, CYP2B6 and CYP2D6 in vitro (human B-lymphoblastoid cell microsomes) and ex vivo (human plasma) [18]; d) Voriconazole: The voriconazole N-oxide metabolite was shown to inhibit both CYP2C9 and CYP3A4 enzyme in a competitive fashion in both human liver microsomes and hepatocytes [19]. From the ensuing topic discussed above, an independent assessment for in vitro CYP inhibition potential of metabolite(s), in addition to parent drug, may be warranted to make an informed risk assessment decision of drugs in development.…”
Section: Introductionmentioning
confidence: 99%